Ocorrência de Plasmodium spp em aves silvestres da família Psittacidae mantidas em cativeio no Brasil. - Nayara de Oliveira Belo (2007)
The occurrence of avian malaria in 127 psittacine birds kept in captivity in two distinct regions in Brazil was evaluated through the direct examination of blood smears and the amplification of the 18SSU rRNA gene of Plasmodium. The results indicate a high occurrence of Plasmodium spp. (36%), without differences among the studied regions. Thirty-nine birds from one of the regions were evaluated during one rainy season and one dry season. However, no significant difference was observed between the prevalence rates of Plasmodium in the two seasons. The most frequently infected avian species were: Ara ararauna (6/10) (60%), Amazona amazonica (3/10) (30%) and Amazona aestiva (28/73) (38,4%). The low parasitemias observed among the infected birds suggest a chronic status of infection in these birds. The sequence analyses of ten isolates indicate a potential occurrence of distinct Plasmodium species among the bird species investigated. The high occurrence of Plasmodium spp. infections in captive birds points out to the need of a better control of importation and exportation of psittacine birds between different regions.